Recent Advances in the Development of Transition Metal-Doped TiO2-Doped Photocatalysts and Electrocatalysts for Hydrogen Evolution Reactions: A Systematic Review - Misriyani Misriyani; Emil Hardiansyah; Isti Yunita (Indonesian Journal of Chemistry and Environment, 2026)
This study conducted a systematic literature review to evaluate the recent development of transition metal-doped TiO₂ catalysts for the hydrogen evolution reaction (HER). A total of 20 selected articles were analyzed using the PRISMA approach to identify the influence of dopant type, catalyst architecture, and synthesis methods on catalytic performance. The results showed that transition metals such as Fe, Ni, Cu, and Mo significantly enhanced HER activity by introducing active sites, improving electrical conductivity, and suppressing electron–hole recombination. Among them, Fe demonstrated the most consistent performance due to its ability to modify the electronic structure of TiO₂. In addition, catalyst architectures such as heterojunctions, nanocomposites, and core–shell structures improved charge separation and increased active surface area. Synthesis methods, particularly hydrothermal techniques, played a crucial role in controlling crystallinity and dopant distribution. Overall, the enhancement of HER performance was governed by the synergistic interaction between dopant type, catalyst structure, and synthesis strategy. These findings highlighted the importance of integrated material design for advancing TiO₂-based catalysts toward sustainable hydrogen production applications.